The Estimated Effect of Physicians' Advice for Smoking Cessation and Assumed Tobacco Retail Price Increase on Smoker's Intention to Quit in Shanghai, China: A Cross-Sectional Study - Wang, Ruiping; Gao, Xiangjin; Qiang, Yan; Yang, Qiong; Li, Xiaopan; Li, Bin (Frontiers in Public Health, 2021)
Background: Tobacco consumption produces a heavy disease burden worldwide, and tobacco price increase, advertisement for tobacco induced harm, graphic warning labels on cigarette packages and physicians’ advice for quitting are policies have been proved as effective smoking cessation measures. But evidence on the estimated effect of physicians’ advice for quitting and assumed tobacco retail price increase on smoking cessation intention among smokers is still limited in China. Methods: From January to April of 2021, we recruited 664 current smokers in Songjiang district of Shanghai by a multistage sampling design. We implemented logistic regression to calculate the Odds Ratio (OR) and 95% confidence interval (CI) to explore how smoking cessation intention would be influenced by the assumed tobacco retail price increase as well as physicians’ advice for quitting, and used the paired tabulation method to identified the salient tobacco control measures among smokers as well. Results: 664 current smokers included 548 male (82.53%), with an average smoking duration of 22.50 years (SD: 11.52 years). 68.79% and 43.67% of current smokers reported smoking cessation intention due to physicians’ advice for quitting and the assumed tobacco retail price increase, respectively. Logistic regression indicated that female smokers (OR=2.85 and 4.55), smokers with previous smoking cessation attempt (OR=3.71 and 3.07), longer smoking duration (OR=2.26 and 2.68), lower smoking intensity (OR=1.82 and 1.69), and heavier tobacco burdens (OR=1.67 and 2.22) had the higher intention of smoking cessation both due to physicians’ advice for quitting and assumed tobacco price increase, respectively. Meanwhile, physicians’ advice for quitting was more effective and acceptable (over 80%) than the assumed tobacco price increase for inducing smokers to consider quitting in Shanghai. Conclusions: Smokers have high intention of smoking cessation in Shanghai, and physicians’ advice for quitting is a potentially more salient tobacco control measure than the assumed tobacco retail price increase. Incorporating smoking duration, intensity, personal burden as well as NCD status of smokers into the implementation of tobacco control measures is beneficial for descending smoking prevalence.